ICE manual of bridge engineering - Parke, Gerard; Nigel Hewson (Thomas Telford, 2008)
The fully revised, restructured and updated second edition of the ICE Manual of Bridge Engineering has been written and edited by a team of leading experts and presents valuable contributions from across the field within a single resource.
1st. ed. published in 2000.
Keywords: Bridges -- Design and construction.; Bridges -- Maintenance and repair.; elektronické knihy; electronic books